An improved analysis of the OECD/NRC PWR MOX/UO2 core transient benchmark with PARCS/Serpent. (April 2022) - Ha, Pham Nhu Viet; Hartanto, Donny; Vu, Thanh Mai; Tran, Vinh Thanh; Tran, Viet-Phu
Highlights: Improved solution of the OECD/NRC PWR MOX/UO2 core transient benchmark was obtained with PARCS/Serpent. Impacts of different diffusion coefficients, radial and axial reflector cross-sections, thermal cut-offs, and nuclear data libraries were analysed. The combined cumulative migration method and 3D reflector model alongside the 0.625 eV cut-off appears to be the best choice. Use of the 4.0 eV cut-off or ENDF/B-VIII.0 library leads to the most conservative transient results. Abstract: This paper presents an improved analysis of the OECD/NRC PWR MOX/UO2 core transient benchmark using the two-step method combining the Monte Carlo code Serpent 2 and nodal kinetics code PARCS. Analyses of the following important factors that can affect the PARCS/Serpent calculations were performed: diffusion coefficients attained with the B1 leakage corrected out-scatter approximation and cumulative migration method (CMM), reflector cross-sections generated with 1D and 3D reflector models, thermal cut-offs for two-group structure (0.625 eV, 1.3 eV, 2.02 eV and 4.0 eV), and nuclear data libraries (ENDF/B-VI.8, ENDF/B-VII.1 and ENDF/B-VIII.0). The results showed that using the CMM method and 3D reflector model alongside the 0.625 eV cut-off is the best choice while using the 4.0 eV cut-off or ENDF/B-VIII.0 library leads to the most conservative transient results. Thus, it is highly recommended that the two-step approach with PARCS/Serpent proposed be applied to improve further transient calculations of PWR MOX/UO2 cores.